A Facile and Efficient Modification of CNTs for Improved Fischer–Tropsch Performance on Iron Catalyst: Alkali Modification. Issue 8 (20th January 2016) - Liu, Renjie; Xu, Yan; Li, Zhenhua; Ma, Xinbin
Abstract: In this paper, a facile and environmentally benign method is used to pretreat carbon nanotubes (CNTs) by alkali modification, which decreases the wall thickness, increases the inner diameter, and improves the graphitization degree of CNTs compared to conventional acid treatment. The iron catalyst supported on alkali modified CNTs shows extraordinary Fischer–Tropsch synthesis (FTS) activity and CO conversion (1.78 and 2.41 times, respectively) compared with those supported on either the acid treated or pristine CNTs. Additionally, the diesel (C10‐20 ) selectivity on Fe/CNTs‐Na is up to 60 %, which is much higher than that calculated from the Anderson–Schulz–Flory distribution (39 %). Similar results are also found by using activated carbon (AC) and N‐doped multiwall carbon nanotubes (NCNTs) as supports for FTS, proving the universal applicability of alkali modification on carbon material. The positive relationship between the C5+ selectivity and C2 −C4 olefin/paraffin ratio of iron catalyst can also be achieved irrespective of the support type. Abstract : Alkali modified carbon nanotubes (CNTs) are reported as a support for an iron‐based Fischer–Tropsch catalyst. This modification can decrease wall thickness, increase inner diameter, and graphitization degree of CNTs. The resulting Fe/CNTs‐Na catalyst displayed extraordinary catalytic performance and remarkably high diesel selectivity.